PPARβ/δ Is Required for Mesenchymal Stem Cell Cardioprotective Effects Independently of Their Anti-inflammatory Properties in Myocardial Ischemia-Reperfusion Injury - Nernpermpisooth, Nitirut; Sarre, Charlotte; Barrere, Christian; Contreras, Rafaël; Luz-Crawford, Patricia; Tejedor, Gautier; Vincent, Anne; Piot, Christophe; Kumphune, Sarawut; Nargeot, Joel; Jorgensen, Christian; Barrère-Lemaire, Stéphanie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Myocardial infarction ranks first for the mortality worldwide. Because the adult heart is unable to regenerate, fibrosis develops to compensate for the loss of contractile tissue after infarction, leading to cardiac remodeling and heart failure. Adult mesenchymal stem cells (MSC) regenerative properties, as well as their safety and efficacy, have been demonstrated in preclinical models. However, in clinical trials, their beneficial effects are controversial. In an experimental model of arthritis, we have previously shown that PPARβ/δ deficiency enhanced the therapeutic effect of MSC. The aim of the present study was to compare the therapeutic effects of wild-type MSC (MSC) and MSC deficient for PPARβ/δ (KO MSC) perfused in an ex vivo mouse model of ischemia-reperfusion (IR) injury. For this purpose, hearts from C57BL/6J mice were subjected ex vivo to 30 min ischemia followed by 1-h reperfusion. MSC and KO MSC were injected into the Langendorff system during reperfusion. After 1 h of reperfusion, the TTC method was used to assess infarct size. Coronary effluents collected in basal condition (before ischemia) and after ischemia at 1 h of reperfusion were analyzed for their cytokine profiles. The dose-response curve for the cardioprotection was established ex vivo using different doses of MSC (3.105, 6.105, and 24.105 cells/heart) and the dose of 6.105 MSC was found to be the optimal concentration. We showed that the cardioprotective effect of MSC was PPARβ/δ-dependent since it was lost using KO MSC. Moreover, cytokine profiling of the coronary effluents collected in the eluates after 60 min of reperfusion revealed that MSC treatment decreases CXCL1 chemokine and interleukin-6 release compared with untreated hearts. This anti-inflammatory effect of MSC was also observed when hearts were treated with PPARβ/δ-deficient MSC. In conclusion, our study revealed that the acute cardioprotective properties of MSC in an ex vivo model of IR injury, assessed by a decreased infarct size at 1 h of reperfusion, are PPARβ/δ-dependent but not related to their anti-inflammatory effects.